Examining the relationship between visitors wildlife value orientation and risk perceptions: a study of the Borneo Pygmy elephant in Sabah, Malaysian Borneo - Naim, Shafinaz; Samdin, Zaiton; Emang, Diana; Lajuni, Nelson; Dousin, Oscar (Macrothink Institute, 2022)
Recently, there has been a growing interest in studying human-elephant conflicts; however, in the case of the Borneo Pygmy elephant, which has only been found in Sabah, Malaysian Borneo has not been thoroughly investigated. Recent studies shows the number of elephants killed as a result of human conflict is on the rise. This study intends to examine the relationship between visitor Wildlife Value orientation (domination and mutualism) towards Borneo Pygmy elephant risk perceptions. 401 survey data was collected from on-site visitors, and PLS-SEM analyses revealed that domination has a significant relationship with risk perception of Borneo Pygmy elephants. Mutualism, on the other hand, does not appear to be related to risk perceptions, according to the study. The findings are beneficial to policymakers in developing programmes that encourage visitors to view the endangered Borneo pygmy elephants in a more positive light, to reducing human-elephant conflicts.